Controle de qualidade físico-químico de comprimidos de ibuprofeno distribuídos em Unidades Básicas de Saúde de Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Quality control is essential to ensure the efficacy, safety, and regulatory compliance of medications, minimizing the risks of adverse effects. Ibuprofen, a widely used nonsteroidal anti-inflammatory drug (NSAID), works by inhibiting cyclooxygenase enzymes (COX-1 and COX-2), reducing eicosanoid synthesis. It is available in various pharmaceutical forms, and the quality of these formulations is crucial to ensure correct dosage and absence of impurities, promoting patient trust and public health. However, variability in the physicochemical quality of ibuprofen tablets can compromise their therapeutic performance. Therefore, local studies are necessary to identify potential quality deviations and contribute to effective health policies. This study aimed to analyze the average weight, friability, and assay of ibuprofen tablets, according to the methods described in the Brazilian Pharmacopeia, 6th edition (2019), and to verify the compliance of these samples with established standards. The physicochemical quality of ibuprofen was evaluated in primary healthcare units (PHU) in Santarém, PA. Samples were collected from eight batches of tablets, totaling 160 units. For the analysis, three tests were performed: average weight (with an allowed variation of ±5%), friability (with a maximum loss of 1.5%), and assay (with a declared content between 90.0% and 110.0%). The results were organized and analyzed using Microsoft Excel software (version 2011). The physicochemical tests showed that the average tablet weights were within the variation limits established by the Brazilian Pharmacopeia, indicating good precision in the compression process. All batches showed a weight loss of less than 1.5% in the friability test, demonstrating the tablets' resistance and the preservation of active ingredients during handling. The determination of ibuprofen content was performed by titration with a 0.1 mol/L NaOH solution, previously standardized. The correction factors found ranged from 0.9811 to 0.9827, ensuring the accuracy of the analyses. The assay results indicated consistency among the samples, reinforcing the importance of quality control to ensure therapeutic efficacy and patient safety. Thus, the study confirmed that the analyzed batches of ibuprofen tablets complied with the required standards, highlighting the relevance of ongoing studies on the quality control of medications in primary care.
Keywords: Controle de Qualidade; Testes Físico-Químicos; Ibuprofeno; CNPQ:: CIÊNCIAS DA SAÚDE